The effect of piracetam on ataxia: clinical observations in a group of autosomal dominant cerebellar ataxia patients - AĞAN YILDIRIM, KADRİYE (BLACKWELL PUBLISHING, 2008)
Objectives: Autosomal dominant cerebellar ataxias are clinically and genetically heterogeneous neurodegenerative disorders. There is no known treatment to prevent neuronal cell death in these disorders. Current treatment is purely symptomatic; ataxia is one of the most disabling symptoms and represents the main therapeutic challenge. A previous case report suggesting benefit from administration of high dose piracetam inspired the present study of the efficacy of this agent in patients with cerebellar ataxia. Piracetam is a low molecular weight derivative of gamma-aminobutyric acid. Although little is known of its mode of action, its efficacy has been documented in a wide range of clinical indications, such as cognitive disorders, dementia, vertigo and dyslexia, as well as cortical myoclonus. The present report investigated the role of high dose piracetam in patients with cerebellar ataxia. Methods: Eight patients with autosomal dominant cerebellar ataxia were given intravenous piracetam 60 g/day by a structured protocol for 14 days. The baseline and end-of-the study evaluations were based on the International Cooperative Ataxia Rating Scale. Results: Statistical analysis demonstrated a significant improvement in the patients' total score (P = 0.018) and a subscale analysis showed statistical significance for only the posture and gait disturbances item (P = 0.018). Conclusion: This study is providing good clinical observation in favour of high dose piracetam infusion to reduce the disability of the patients by improving their gait ataxia.
Keywords: ataxia; autosomal dominant; cerebellar; piracetam; treatment; SPINOCEREBELLAR ATAXIA